Driving financial inclusion of the unbanked population in Bangladesh–a study of IDLC Finance’s digital deposit scheme through bKash - Elora, Mashiat Hasan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.